Classics on screen : ancient Greece and Rome on film - Blanshard, Alastair; Shahabudin, Kim. (Bristol : Bristol Classical, 2011)
- Establishing the conventions : Cleopatra (1934)##- The Roman epics of classical Hollywood : Quo vadis (1951)##- Peplum traditions : Hercules (1958)##- Roman history on screen : Spartacus (1960)##- Greek history on screen : The 300 Spartans (1962)##- Myth and the fantastic : Jason and the Argonauts (1963)##- Art cinema : Fellini-Satyricon (1969)##- Satirising cine-antiquity : Monty Python's life of Brian (1979)##- The Disney version : Hercules (1997)##- The return of the epic? : Gladiator (2000).
boek